Kato-Katz slide preservation technique: Extension of viability and the benefits for schistosomiasis control programs - Loyo, Rodrigo; Gomes, Elainne Christine Souza; Pieri, Otavio Sarmento; Oliveira, Emília Carolle Azevedo de; Nascimento, Wheverton Ricardo Correia; Barbosa, Constança Simões (Experimental parasitology, 2024)
The World Health Organization recommends the use of the Kato-Katz method in the procedures of schistosomiasis control programs. Studies show the importance of a fast reading of the slides due to the decline of their viability, with the appearance of fungi or desiccation of the sample, which hinders diagnosis. It is necessary to establish a procedure to improve the long-term preservation of these Kato-Katz slides in order to accomplish the following: (1) preserve the slides for future quality control procedures and readings; (2) allow for the production of durable materials for training; and (3) train health professionals involved in diagnosing schistosomiasis. Therefore, this study aims to test a slide preservation methodology for these purposes. The results showed that the modifications made to the experimental slides demonstrated that egg loss was within the expected range and the limit accepted by quality control standards, as well as improved the diagnostic durability of the slides during the preservation times tested. We concluded that the application of the preservation technique to the slides promoted stabilization and permanence for long-term storage.